Avaliação ecotoxicológica de concentrações ambientais de atrazina e glifosato, isolados e em mistura, em diferentes organismos-teste - Bordin, Eduarda Roberta (2021)
The Brazilian agricultural sector contributes to a high consumption of pesticides, with greater amounts and mixtures of herbicides used in crops in order to increase productivity. Many studies address the phytotoxicity obtained through the association of a series of herbicides for some weeds, however, there is still a gap related to the ecotoxicological aspects of these mixtures. The present work aimed to evaluate the ecotoxicity of the active ingredients and commercial products of the herbicides atrazine (2 and 25 µg.L-1) and glyphosate (65 and 160 µg.L-1), isolated and when mixed (2+ 65 and 25 + 160 µg.L-1), in concentrations of environmental relevance. The exposure of A. aegypti to herbicides did not result in immobility of the test organisms after acute exposure (24 h). The chronic exposure (21 days) of three generations of D. magna to herbicides, resulted in effects on the survival, sexual maturation and reproduction of the organisms, in addition to effects on the biochemical biomarkers catalase and glutathione S-transferase. A. cepa was a good biological model for evaluating the tested concentrations, since after 96 h of exposure to herbicides, cytotoxic, genotoxic and mutagenic effects were verified, with chromosomal buds and adhesions being the abnormalities most frequently observed, demonstrating the aneugenic potential of the herbicides. In the test with R. quelen embryos it was possible to observe significant effects (p<0.05) referring to the deformities caused by herbicides throughout the 96-hour exposure, where axial and fin damage were the most frequent, and effects were verified on the biochemical biomarkers superoxide dismutase, catalase, glutathione S-transferase and acetylcholinesterase. This work made it possible to observe different sensitivities for each biological model, highlighting the mixture of herbicides, responsible for more significant responses (p<0.05) in all evaluated non-target organisms. In addition, it was possible to verify differences between the tested concentrations, and above all, to compare the effects caused by the active ingredients and commercial formulations. Considering that these compounds can act indirectly on living beings, it is necessary to understand the effects and anticipate the repair of possible damage caused to non-target species.